2021
DOI: 10.7554/elife.66143
|View full text |Cite
|
Sign up to set email alerts
|

The EMT transcription factor Snai1 maintains myocardial wall integrity by repressing intermediate filament gene expression

Abstract: The transcription factor Snai1, a well-known regulator of epithelial-to-mesenchymal transition, has been implicated in early cardiac morphogenesis as well as in cardiac valve formation. However, a role for Snai1 in regulating other aspects of cardiac morphogenesis has not been reported. Using genetic, transcriptomic, and chimeric analyses in zebrafish, we find that Snai1b is required in cardiomyocytes for myocardial wall integrity. Loss of snai1b increases the frequency of cardiomyocyte extrusion away from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
4
11
0
Order By: Relevance
“…Our results highlight its major role at the tissue level where it impacts cell tension mainly at the CM interface by increasing cell contractility. In zebrafish, it was shown that invalidation of the snaib factor induced extrusion of cardiomyocytes with increased contractility and an alteration in the desmb gene (orthologue of the des gene in humans) ( Gentile et al, 2021 ). Overexpression of desmin recapitulates this process and highlights its role in maintaining the myocardial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight its major role at the tissue level where it impacts cell tension mainly at the CM interface by increasing cell contractility. In zebrafish, it was shown that invalidation of the snaib factor induced extrusion of cardiomyocytes with increased contractility and an alteration in the desmb gene (orthologue of the des gene in humans) ( Gentile et al, 2021 ). Overexpression of desmin recapitulates this process and highlights its role in maintaining the myocardial wall.…”
Section: Discussionmentioning
confidence: 99%
“…4g). These genes are essential for myocardial differentiation, cardiac primordia migration, as well as cardiac valve and second heart field morphogenesis (Ellertsdottir et al 2012;Gentile et al 2021;Nevis et al 2013;Sam et al 2020;Schindler et al 2014). Especially the zinc finger transcription factors (gata4/5/6).…”
Section: Discussionmentioning
confidence: 99%
“…The dataset used comprised HNSCC mRNA-seq data from TCGA. A heat map of the correlation between S100 family genes and EMT-related genes of SNAI1 ( 18 ), VIM ( 19 ), TWIST ( 19 ), CDH1 ( 20 ), CDH2 ( 20 ) were performed by the Spearman correlation via R software package ggstatsplot ( 21 ), and is displayed by the R software package pheatmap ( 21 ). A P value of less than 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%